Asesmen Psikologi sebagai Alat Bantu Konselor dalam Memahami Dinamika Individu - Heti Ainun Mardhiatus Sholihah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Psychological assessment is an essential component in the guidance and counseling process, as it serves as a tool to help counselors comprehensively understand the dynamics of an individual. Through various assessment techniques, both quantitative—such as psychological tests—and qualitative—such as interviews and observations—counselors can identify psychological factors that influence the behavior, thoughts, and emotions of the counselee. The purpose of this article is to explore how psychological assessment can be effectively used by counselors to understand an individual’s internal condition, as well as how it supports the accuracy of counseling interventions. The findings indicate that the ethical and professional use of assessments can enhance understanding of the counselee and serve as a foundation for developing personalized and effective counseling strategies.